2019
DOI: 10.2140/moscow.2019.8.103
|View full text |Cite
|
Sign up to set email alerts
|

On the quotient set of the distance set

Abstract: Let Fq be a finite field of order q. We prove that if d ≥ 2 is even and E ⊂ F d q with |E| ≥ 9q d 2 then 2000 Mathematics Subject Classification. 11T24, 52C17.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…In addition, if we assume that k is odd and q ≡ 3 mod 4, then the condition |E| ≥ Cq 3d− 4 4 would be enough. We remark here that when E = A × A for A ⊂ F n q or E = A 2n for A ⊂ F q , the cardinality of φ(E, E) has been studied in earlier papers by Iosevich, Koh, and Parshall [14], Pham and Suk [24], respectively, with different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, if we assume that k is odd and q ≡ 3 mod 4, then the condition |E| ≥ Cq 3d− 4 4 would be enough. We remark here that when E = A × A for A ⊂ F n q or E = A 2n for A ⊂ F q , the cardinality of φ(E, E) has been studied in earlier papers by Iosevich, Koh, and Parshall [14], Pham and Suk [24], respectively, with different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, Iosevich, Koh, and Parshall [9] proved that the exponent d/2 holds for the quotient set of the distance set, which is defined by…”
mentioning
confidence: 99%
“…The statement of their result is as follows. [9]). Let F q be a finite field of order q, and E be a set in F d q .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sums of the distance sets: In the spirit of the Erdős-Falconer distance problem, Iosevich, Parshal, and the first listed author [34] recently studied a related interesting question: how large does a subset A of F d q need to be such that the quotient set of the distance set covers all elements in the field? They showed that if d ≥ 2 is even and |A| ≫ q d/2 , then we have…”
Section: Three-distance Problems Over Finite Spacesmentioning
confidence: 99%